The wet electrostatic precipitator as a cause of mist formation—Results from the amine-based post-combustion capture pilot plant at Niederaussem. (October 2015) - Moser, Peter; Schmidt, Sandra; Stahl, Knut; Vorberg, Gerald; Lozano, Gustavo A.; Stoffregen, Torsten; Richter, Torsten
Highlights: The cause of mist formation by a wet electrostatic precipitator was investigated. Solid nano-particles <300 nm act as nuclei for aerosol formation. Aerosol formation is more complex than a simple SO3 /H2 SO4 -ruled mechanism. The wet electrostatic precipitator can generate ultrafine particles/droplets. PCC emission reduction technologies need to remove aerosol-forming nuclei. Abstract: The investigation of emission formation mechanisms – in particular for aerosol driven mist formation – and also the development and testing of emission reduction measures for amine based post-combustion capture are essential parts of the joint development programme of BASF, Linde and RWE Power at the post-combustion capture pilot plant at Niederaussem. During more than 28, 000 operating hours with BASF's innovative capture technology OASE blue ® several emission mitigation systems have been evaluated under real power plant conditions. A wet electrostatic precipitator (WESP) is often regarded as a suitable option to avoid mist formation. In contrast to this, our investigations have shown that the WESP can cause aerosol formation by increasing the number concentration of ultrafine particles/droplets in the flue gas. Our results also indicate that this highly negative, voltage-dependent effect cannot be explained by a measurable increase of the SO3 concentration downstream of the WESP at the entrance of the CO2 absorber. Varying concentrations of SO2 in the flue gas – which can react to SO3 by ozone that is generated in the high-voltage field of the WESP – does not verifiably influence the entrainment. Low emission levels can be achieved by a special pre-treatment of the flue gas and by the so-called Dry Bed configuration.